REVISITING UNIVERSAL GRAMMAR - Meisel, Jürgen M. (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper sketches various specific scenarios within the Principles and Parameter Theory under which the question of whether Universal Grammar remains accessible to second language learners should be addressed. It also discusses some implications of several approaches to this issue and offers some speculation as to how the question is to be reformulated in the context of the Minimalist Program.